Patterns of Fracture - Causing Traffic Injuries and Accuracy of ICD-10 External Cause Coding: A Case Study at a Type B Hospital in Semarang - Dyah Ernawati; Novenda Kusuma Putri; Maulana Tomy Abiyasa (Dian Nuswantoro Semarang, 2026)
Traffic accidents, particularly motorcycle crashes, constitute a leading cause of musculoskeletal fractures in urban Indonesia, yet inaccurate ICD-10 external cause coding undermines epidemiological surveillance and injury prevention efforts. This study aimed to analyze patterns of accident causes leading to fractures and evaluate the accuracy of external cause coding in medical records at a Type B hospital in Semarang. A quantitative descriptive study was conducted using retrospective observation of 88 inpatient medical record documents for fracture cases in 2022, sampled via the Slovin formula from a population of 757 cases. Data on accident patterns (type, location, activity) and coding accuracy were extracted per ICD-10 guidelines (V01-Y98), with conformity assessed descriptively based on completeness to the fifth character and alignment with clinical chronology. Motorcycle accidents dominated (58.8%), primarily traffic-related driver injuries (72.0%), followed by falls (31.8%); non-traffic incidents frequently occurred at home (74.3%). Fracture coding accuracy reached 69.3%, but external cause coding was critically low at 19.3%, with major discrepancies in accident type (56.3%), location (33.8%), and activity (9.9%). These findings highlight systemic coding deficiencies that distort injury epidemiology data. Enhanced coder training, standardized chronology documentation, and hospital policies for external cause coding are recommended to improve data quality for public health interventions.